First report of alkaptonuria in Peru - Daniel Guillén-Mendoza; María Quiroga de Michelena (Revista Peruana de Medicina Experimental y Salud Pública, 2014)
Alkaptonuria is an inborn error of metabolism caused by deficiency of homogentisate 1,2-dioxygenase (HGD) which produces an excess of homogentisic acid (HGA). A case is presented of a 57 year old woman whose urine has turned black since birth. For 9 years she presented a greenish pigmentation in her nail beds that did not improve with antifungal treatments, and in the last 9 months she showed worsening large joint osteoarthritis. This situation forced her to use a wheelchair due to the intense pain caused by osteoarthritis in her hips and lumbar spine. From the description of symptoms, her urinary HGA was measured which confirmed the diagnosis of alkaptonuria. Analgesics and a diet without tyrosine-containing products were suggested. The patient was also referred for hip replacement surgery. This is the first reported case of alkaptonuria in Peru.